Motorway architecture - Verdiana Peron (In Situ)
Nowadays, the facilities of large-scale infrastructures are subject to unprecedented preservation challenges. The protection of these buildings needs an innovative approach. This will be possible through the establishment of new public policies which acknowledge them within the 20th-century cultural heritage. In this field, the Italian motorway service chain was a unique experience in Europe. It was an emblem of a new post-war national identity as well as a symbol of architectural and engineering experimentation. These buildings (1958-1972) are currently threatened by invasive interventions caused by the non-recognition of their cultural value. The current study by the author is comparing, for the first time, the original features of the motorway restaurants with the current situation. The majority of the buildings have been demolished or significantly altered. The paper examines three case studies of great interest: the rest-stops in Novara, Soave, and Lainate. The essay highlights the link between recognition of the cultural value and subsequent operational practices, and also discusses the positions of the stakeholders. Moreover, the essay provides new insights into the stance of public policies and preservation procedures. The connection between knowledge and enhancement of these buildings is the key point of the research. Its final aim is to give theoretical tools and methods to guide future interventions on such heritage.